Association Between Urbanicity and Dementia in China: A Population-Based Study. (9th July 2020) - Luo, Yanan; Zhao, Yihao; Pang, Lihua; Guo, Chao; Liang, Richard; Zheng, Xiaoying
Abstract: Objectives: This study investigated the relationship between urbanicity and dementia and predicted its nonlinear pattern among Chinese adults aged 50 years and older. Methods: This study used data from the Second National Sample Survey on Disability, which was implemented from April 1 to May 31, 2006 across China. Dementia status was determined by a 2-stage process: the combination of self-reports or family members' reports and an onsite medical diagnosis by experienced specialists based on the International Statistical Classification of Diseases and Related Health Problems 10th Revision Symptom Checklist for Mental Disorders. Logistic regression models were used to examine the relationship between urbanicity and dementia, and restricted polynomial spline regression models were plotted to examine the nonlinear exposure–response relationship of urbanicity and dementia. Results: Logistic regression results showed that an increase of 10% in the degree of urbanization was associated with a 73% decrease in the odds of dementia after adjusting for covariates, particularly area-level socioeconomic variables. This observed association was stronger in the younger age group, and this age group difference was only present in women. Spline regression findings suggested a nonlinear exposure–response relationship between urbanicity and the odds of dementia. Areas with very high levels of urbanization were associated with increased odds of dementia. Conclusions: These findings highlight the necessity to properly examine the nuanced relationship between urbanicity and mental health, especially for women in the younger age group. Notably, there were increased odds of dementia at very high levels of urbanicity.